Analisis Analisis Strategi Pemasaran Dalam Meningkatkan Daya Saing Perusahaan - Romi Saputra; Markoni Aswan; Muhammad Noor Armi (Journal of Trends Economics and Accounting Research, 2023)
The rapid development of business has led to sharp competition among companies. Therefore it is necessary to make efforts to improve quality to produce products that are in demand and in accordance with the wishes of consumers. This study aims to determine the marketing strategies used by companies to increase competitiveness and the constraints faced by companies in increasing competitiveness. This research is a descriptive research with qualitative methods. Sources of data in this research consist of primary data obtained through observations and interviews with related company owners, and secondary data obtained through literature related to research. The sample used in this study amounted to 35 respondents. The results showed that the marketing strategy analysis of PT. Kinarya Selaras Solusi to increase company competitiveness through the 4P marketing mix: Product, price, promotion, place has provided a lot of strength and knowledge to take advantage of existing opportunities, with the formulation of an analysis of strengths, weaknesses, opportunities and threats so that it can be formulated that the right strategy for the company is a low-cost strategy, so that it can be implemented with product policies, pricing policies, promotion policies by marketing products through advertising such as TV or radio, sales promotions with direct sales going wide, promotional publicity events using banners , and place policies. So that it can produce feedback that can be mutually accepted and given by both consumers and PT. Kinarya Selaras Solutions that influence one another.